2016
DOI: 10.1108/mip-11-2015-0216
|View full text |Cite
|
Sign up to set email alerts
|

Message involvement and attitude towards green advertisements

Abstract: Purpose Previous green research shows conflicting results regarding the relationship between environmental concern and persuasion. It has also largely overlooked the role of situational involvement. The purpose of this paper is to aim to show that message involvement influences attitude towards green advertisements. Design/methodology/approach To test the proposed model, an experimental study based on a sample of young adults in an emerging economy was used to investigate if situational involvement can produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 90 publications
0
22
0
1
Order By: Relevance
“…Their results showed an overall favorable impact on the brand attitude of the green brand positioning [22]. In an experimental study examining green advertisements, Fernando et al [23] found that consumers responded to messages that evoked an element of concern for the state of the environment. This information helped advertisers to create messages that prompted greater consumer involvement.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 96%
“…Their results showed an overall favorable impact on the brand attitude of the green brand positioning [22]. In an experimental study examining green advertisements, Fernando et al [23] found that consumers responded to messages that evoked an element of concern for the state of the environment. This information helped advertisers to create messages that prompted greater consumer involvement.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 96%
“…The basic premise of persuasion models is that attitude and intention changes depend upon the likelihood that a persuasive issue or argument will be positively evaluated by the receiver (Petty and Cacioppo, 1986 ; Eagly and Chaiken, 1993 ). Message evaluation has a direct effect on receivers' attitude and intention toward the behavior recommended in the message (e.g., Cauberghe et al, 2009 ; Fernando et al, 2016 ), and this effect has been demonstrated also when the recommended behavior regards physical activity (Jones et al, 2003 ). In the present study, we moved from the assumption that the effect of message framing on attitude and intention would at least partially depend on how differently framed messages would be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Higher intensity of threat will lead to greater fear arousal (an emotional response) and have an impact on perceived severity and vulnerability. This has been documented in health domains such as cancer (McMath and Prentice-Dunn, 2005), and green marketing (Fernando et al, 2016). Hence, higher intensity of threat will produce heightened levels of perceived severity and perceived vulnerability.…”
Section: Threat Appealmentioning
confidence: 97%
“…For instance, Fernando et al (2016) extend the Protection Motivation Theory (PMT) to green marketing even while they do not contribute to the PMT/EPPM by extending it fundamentally.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation